Makna dan Fungsi Tuturan Adat Keu Laka di Desa Serubeba Kecamatan Rote Timor Kabupaten Rote Ndao: Indonesia - Fallo, John Darwis; Boimau, Sanhedri (Ciencias : Jurnal Penelitian dan Pengembangan Pendidikan, 2023)
The purpose of this study was to describe the meaning contained in the Keu Laka Customary Ritual Speech in Serubeba Village, East Rote District, Rote Ndao District, to describe the functions in the Keu Laka Customary Ritual Speech in Serubeba Village, East Rote District, Rote Ndao District. The approach in this study uses a cultural linguistic theory approach. Data collection techniques using interview and observation techniques. The data analysis technique uses a qualitative descriptive technique. The results of the study found various linguistic meanings, including: the meaning of supplication, the meaning of adoration, and linguistic functions, including: expressive function, conative function.